2008
DOI: 10.1074/jbc.m800224200
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer of Zeste Homologue 2 (EZH2) Down-regulates RUNX3 by Increasing Histone H3 Methylation

Abstract: Overexpression of enhancer of zeste homologue 2 (EZH2) occurs in various malignancies and is associated with a poor prognosis, especially because of increased cancer cell proliferation. In this study we found an inverse correlation between EZH2 and RUNX3 gene expression in five cancer cell lines, i.e. gastric, breast, prostate, colon, and pancreatic cancer cell lines. Chromatin immunoprecipitation assay showed an association between EZH2 bound to the RUNX3 gene promoter, and trimethylated histone H3 at lysine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
142
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(150 citation statements)
references
References 32 publications
5
142
3
Order By: Relevance
“…This also suggests that CLDN4 is not a direct target of EZH2 in contrast to RUNX3 or E-cadherin the expressions of which have been reported to be directly regulated by EZH2. 41,42 As shown in Figure 5e, DZNep/TSA caused a significant increase in active H3K4me3, H3Ac and H4Ac along with producing a significant reduction in H4K20me3 and H3K9me3 levels in SNU638 cells (Po0.05). Unexpectedly, H3K27me3 was not decreased by DZNep/TSA, suggesting that loss of the EZH2-mediated H3K27me3 mark in SNU638 cells may not be responsible for CLDN4 derepression by DZNep/TSA.…”
Section: Bivalent Histone Modifications Are Associated With Cldn4 Repmentioning
confidence: 94%
“…This also suggests that CLDN4 is not a direct target of EZH2 in contrast to RUNX3 or E-cadherin the expressions of which have been reported to be directly regulated by EZH2. 41,42 As shown in Figure 5e, DZNep/TSA caused a significant increase in active H3K4me3, H3Ac and H4Ac along with producing a significant reduction in H4K20me3 and H3K9me3 levels in SNU638 cells (Po0.05). Unexpectedly, H3K27me3 was not decreased by DZNep/TSA, suggesting that loss of the EZH2-mediated H3K27me3 mark in SNU638 cells may not be responsible for CLDN4 derepression by DZNep/TSA.…”
Section: Bivalent Histone Modifications Are Associated With Cldn4 Repmentioning
confidence: 94%
“…More specifically, reintroduction of miR-101 or knockdown of EZH2 expression was sufficient to reduce H3K27 trimethylation and increase RUNX3 mRNA levels. In the same vein, Fujii et al (2008) found that EZH2 binds to the RUNX3 promoter, resulting in upregulation of H3K27 methylation and concomitant downregulation of RUNX3 expression (Fujii et al, 2008). Recently, Lee et al (2009) extended this finding by showing that hypoxia-induced upregulation of G9a histone methyltransferase and HDAC1 expression also cause epigenetic RUNX3 silencing through H3K9 methylation and decreased H3 acetylation at RUNX3 promoter.…”
Section: Putative Causes Of Runx3 Hypermethylationmentioning
confidence: 96%
“…Although it is unclear what causes aberrant methylation of RUNX3, RUNX3 was recently reported to be silenced in gastric, breast, prostate, colon, and pancreatic cancer cell lines by another epigenetic mechanism-enhancer of Zeste Homologue 2 (EZH2)-mediated histone methylation (Fujii et al, 2008). The EZH2 oncogene is a component of Polycomb-repressor complex 2, which is required for stem cell pluripotency and self-renewal.…”
Section: Putative Causes Of Runx3 Hypermethylationmentioning
confidence: 99%
“…Mislocalisation of RUNX3 protein to the cytoplasm is another mechanism by which RUNX3 can be inactivated in gastric and breast cancers Lau et al, 2006). Overexpression of the enhancer of zeste homologue 2 (EZH2) protein was recently shown to downregulate RUNX3 expression by increasing histone H3 methylation, thus providing yet another mechanism for inactivation of RUNX3 (Fujii et al, 2008). As might be expected, if RUNX3 were behaving as a tumour suppressor, the decreased expression of this protein in gastric (Wei et al, 2005), lung (Araki et al, 2005) and oesophageal (Sakakura et al, 2007) cancers has been associated with worse patient outcome.…”
mentioning
confidence: 99%